Tahapan Penyusunan Kurikulum Pelatihan Vokasi Kejuruan Teknik Listrik BBPVP Serang di Era Revolusi Industri 4.0 - Sachlan, M. Gizwa Afdallah; Sudrajat, Indra (Lembaga Yasin AlSys, 2025)
The Fourth Industrial Revolution presents significant challenges to the workforce, as many conventional jobs are being replaced by automation and digitalization, necessitating adjustments in vocational training systems. This study aims to examine the stages of vocational training curriculum development in electrical engineering at the Center for Vocational Training and Productivity Development (Balai Besar Pelatihan Vokasi dan Produktivitas/BBPVP) Serang in response to the demands of the Fourth Industrial Revolution. A qualitative approach was employed, with data collected through in-depth interviews with the Sub-Coordinator of Competency Development at Intala and electrical engineering instructors, as well as through document analysis. The findings reveal that curriculum development begins with identifying training needs through a Training Need Analysis (TNA), which is then formulated into training programs. The study also identifies several challenges in curriculum implementation, including limited instructor competencies in keeping pace with technological advancements and the mismatch between available training equipment and current industry requirements. These findings underscore the importance of strategies to enhance instructor capacity and strengthen collaboration between training institutions and industry to produce vocational curricula that are both adaptive and technologically relevant.